2017
DOI: 10.1111/jpn.12802
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo heifers selected for lower residual feed intake have lower feed intake, better dietary nitrogen utilisation and reduced enteric methane production

Abstract: This study was conducted to evaluate the utilisation of the residual feed intake (RFI) as a feed efficiency selection tool and its relationship with methane emissions. Eighteen Murrah buffalo (Bubalus bubalis) heifers were fed ad libitum with total mixed ration (TMR) for 120 days. Based on linear regression models involving dry matter intake (DMI), average daily gain (ADG) and mid-test metabolic body size (MBW ), heifers were assigned into low and high RFI groups. The RFI varied from -0.09 to +0.12 kg DM/day w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Butyrate is the major energy substrate for colonocytes, and provides many benefits to heifer calves such as improved epithelial tight junctions and reduced inflammatory status [42]. Blautia and Succinivibrio produce propionate which competes with methanogens for H 2 [43], leading to less enteric methane production in M-eff buffalo heifers [44]. Absorption of propionate by colonocytes would provide a key hepatic gluconeogenic precursor to heifers, hence, indirectly increasing the supply of glucose from what is absorbed from the lumen of the small intestine [45].…”
Section: Hindgut Microbiome and Metabolome During The Preweaning Perimentioning
confidence: 99%
“…Butyrate is the major energy substrate for colonocytes, and provides many benefits to heifer calves such as improved epithelial tight junctions and reduced inflammatory status [42]. Blautia and Succinivibrio produce propionate which competes with methanogens for H 2 [43], leading to less enteric methane production in M-eff buffalo heifers [44]. Absorption of propionate by colonocytes would provide a key hepatic gluconeogenic precursor to heifers, hence, indirectly increasing the supply of glucose from what is absorbed from the lumen of the small intestine [45].…”
Section: Hindgut Microbiome and Metabolome During The Preweaning Perimentioning
confidence: 99%
“…Feed cost, account for 60-70% of the total cost of the modern poultry industry, has become one of the most important factors restricting the development of the poultry industry. A strategy to improve feed efficiency is a high priority for the poultry industry to reduce feed costs and nitrogen excretion [1]. Residual feed intake (RFI) has become a sensitive and accurate indicator of feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted to evaluate the utilization of the residual feed intake (RFI) as a feed efficiency selection tool and its relationship with methane emissions, [13] reported that the selection of more efficient buffalo heifers has multiple benefits, such as decreased feed intake and less emission of methane.…”
Section: Discussionmentioning
confidence: 99%